1959
DOI: 10.1084/jem.109.6.523
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Tubercle Bacillus-Monocyte Relationship

Abstract: Although various observations (1-5) have failed to relate serum antibody to resistance against tuberculosis, these findings need not preclude a role for humorM factors in an as yet indeterminate and possibly rather complex pattern of resistance. The participation of humoral factors in resistance to tubercle bacilli was indicated by the observation that the sera of animals immunized with the BCG strain of tubercle bacillus contained a substance which protected the monocytes of these immunized animals against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1959
1959
1976
1976

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Furthermore the effect was non-specific, for MN derived from rabbits vaccinated with BCG were protected against tubercle bacilli when cultivated in media containing immune sera derived from animals immunized with antigenic materials from Salmonella, Brucella, or Mycobacteria (31). The protective factor was not in the globulin fraction and appeared in the serum 5 days after intradermal injection into rabbits of either live or heat-killed BCG (32). The findings reported suggest that there exist more ways than hitherto recognized by which the immune response may influence and alter interactions between phagocytic cells and pathogens.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore the effect was non-specific, for MN derived from rabbits vaccinated with BCG were protected against tubercle bacilli when cultivated in media containing immune sera derived from animals immunized with antigenic materials from Salmonella, Brucella, or Mycobacteria (31). The protective factor was not in the globulin fraction and appeared in the serum 5 days after intradermal injection into rabbits of either live or heat-killed BCG (32). The findings reported suggest that there exist more ways than hitherto recognized by which the immune response may influence and alter interactions between phagocytic cells and pathogens.…”
Section: Discussionmentioning
confidence: 95%
“…events were dissociable, and production of protective serum factor was more readily achieved than development of cellular resistance (5). Consequently, if the present successful transfers depended on active induction of cellular resistance in recipients by bacilli or bacillary antigens, there should be simultaneous appearance of protective serum factor in recipients.…”
Section: Behavior Of Recipient Serum In Tests Formentioning
confidence: 99%
“…Our own investigations involving in vitro cultures of infected histiocytes have shown that peritoneal exudate cells of normal and immunized rabbits could modify virulent tubercle bacilli, thereby reducing bacillary virulence for mice and inducing changes in certain other bacterial attributes (4). Although these modifications of virulent tubercle bacilli occurred after interaction of bacilli with either normal or immune histiocytes, only immune histiocytes were able to alter virulent tubercle bacilli to the extent where they lost the ability to necrotize the histiocytes themselves (5); this latter observation may be indicative of a greater capacity of immune histiocytes to modify bacillary virulence. Additional evidence for the concept of acquired cellular resistance in tuberculosis may be found in the recent observations of Sever (6) that immune histiocytes will passively transfer resistance to tuberculosis in the whole animal.…”
mentioning
confidence: 99%
“…In this respect, immune-passaged bacilli (i.e., bacilli obtained from an immune system) seemed more sensitive than normal-passaged bacilli. Whether this was the result of a greater modification of bacilli by immune cells was not established in these investigations, but it is of interest to note than an earlier report (9) had demonstrated that immune-passaged bacilli, but not normal-passaged bacilli, failed to cause degeneration of normal rabbit monocytes; it is therefore a possibility that immune monocytes were more effective in modification of virulent bacilli and that the inability to demonstrate marked differences in mouse virulence between normal-passaged and immune-passaged bacilli in these studies may possibly be a reflection of the relative insensitivity of mice, as opposed to monocytes, to small differences in virulence.…”
Section: Discussionmentioning
confidence: 85%
“…An earlier paper (9) has shown that passage of virulent tubercle bacilli in an immune system (monocytes of BCG-immunized rabbits cultivated in homologous immune serum medium) resulted in decreased capacity of bacilli to induce degeneration of normal monocytes.…”
mentioning
confidence: 99%